2003
DOI: 10.1002/ajmg.a.20428
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar ataxia type 2 (SCA2) presenting with ophthalmoplegia and developmental delay in infancy

Abstract: An 11-year-old boy was evaluated for progressive ataxia, cognitive deterioration, and ophthalmoplegia. The child initially presented with abnormal eye movements at the age of 2 months and was noted to have developmental delay at 6 months. At the age of 7 years, he developed ataxia and cognitive impairment, and subsequently manifested dysphagia and incontinence. The pertinent family history included gait difficulty in the paternal grandmother. At the age of 11, his general physical examination was normal. On ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Several clinical investigations disclosed the frequency of dementia in SCA2 patients to be between 19 and 42% [10,16,17,18], although in a comparison of various SCAs, Bürk et al [12] did not find significantly lower scores on neuropsychological tests in SCA2 patients. It has been reported that SCA2 patients have various cognitive disorders, such as developmental delay [19] and olfactory impairment [20]. In another study, Bürk et al [21] systematically addressed the issue of cognitive function in genetically confirmed SCA2 by means of comprehensive neuropsychological testing.…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%
“…Several clinical investigations disclosed the frequency of dementia in SCA2 patients to be between 19 and 42% [10,16,17,18], although in a comparison of various SCAs, Bürk et al [12] did not find significantly lower scores on neuropsychological tests in SCA2 patients. It has been reported that SCA2 patients have various cognitive disorders, such as developmental delay [19] and olfactory impairment [20]. In another study, Bürk et al [21] systematically addressed the issue of cognitive function in genetically confirmed SCA2 by means of comprehensive neuropsychological testing.…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%
“…He presented with progressive extrapyramidal manifestations, slow eye saccades and cognitive impairment. To our knowledge, our proband is the second case after the report of Moretti et al [13] with infantile onset SCA2 and intermediate CAG repeats expansion. Moreover, the unique presentations of polyphagia and obesity at the mid phase of the disease in this family highlight the previous report on the putative contribution of ataxin 2 protein in the development of obesity [10].…”
Section: Introductionmentioning
confidence: 56%
“…Further, infantile and childhood onset SCA2 were assigned in three patients; 64 and 57 repeats were reported in two cases with onset of neurological symptoms at 6 and 8 years old, respectively [3,15]. The third patient had 62 CAG repeats and manifested with abnormal eye movements at the age of 2 months associated with non-specific developmental delay while ataxia and cognitive impairment appeared at 7 years of age [13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is an inverse correlation between the number of repeats, in the pathological range, and the age of onset of the disease (Schols et al, 1997). Specifically, larger expansions (from 130 to more than 200 CAG repeats) are detected in rare patients with the infantile and juvenile forms of SCA2 (Babovic-Vuksanovic et al, 1998;Mao et al, 2002;Moretti et al, 2004), whereas the more common smaller expansions (between 34 and 57 CAG repeats) are detected in patients with the late-onset forms of the disease appearing in adult life, by the age of about 20-40 years (Moretti et al, 2004). As it is expected for a dynamic mutation, the larger expansions of CAG repeats seen in the early forms of SCA2 originate as aberrant gametogenesis events occurring in one of the two parents bearing a repeat number in the ATXN2 gene typical of the late-onset forms (Mao et al, 2002).…”
Section: Introductionmentioning
confidence: 99%